North–South container port competition in Europe: The effect of changing environmental policy. (June 2016) - van Hassel, Edwin; Meersman, Hilde; Van de Voorde, Eddy; Vanelslander, Thierry
Abstract: This article examines environmental policy impacts on competition between the European container ports in the Hamburg–Le Havre range on the one hand and the Mediterranean ports on the other. More in particular, two scenarios are considered: the internalisation of external cost on the European hinterland and the establishment of a Sulphur Emission Control Area (SECA) in the North Sea region. Geographically, applications are made for container loops from both Asia and South America to Europe. A total chain model is applied that incorporates the maritime, port and hinterland legs of the supply chain. The calculations show that the effects of either policy option would not significantly impact on the theoretical captive hinterland of respectively the Hamburg–Le Havre range and the ports of the Mediterranean, as the effects measured are smaller than the error margin of the model applied. Additionally, it is found that the impacts of the two policy options on competition between ports in the Hamburg–Le Havre range and the Mediterranean ports would differ for the two container loops considered.